CN102867978B - Flow energy storage battery structure - Google Patents

Flow energy storage battery structure Download PDF

Info

Publication number
CN102867978B
CN102867978B CN201110186221.9A CN201110186221A CN102867978B CN 102867978 B CN102867978 B CN 102867978B CN 201110186221 A CN201110186221 A CN 201110186221A CN 102867978 B CN102867978 B CN 102867978B
Authority
CN
China
Prior art keywords
electrode
plate
battery
energy storage
flow energy
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Expired - Fee Related
Application number
CN201110186221.9A
Other languages
Chinese (zh)
Other versions
CN102867978A (en
Inventor
张华民
刘涛
赖勤志
刘宗浩
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Dalian Institute of Chemical Physics
Dalian Rongke Power Co Ltd
Original Assignee
Dalian Institute of Chemical Physics
Dalian Rongke Power Co Ltd
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Dalian Institute of Chemical Physics, Dalian Rongke Power Co Ltd filed Critical Dalian Institute of Chemical Physics
Priority to CN201110186221.9A priority Critical patent/CN102867978B/en
Publication of CN102867978A publication Critical patent/CN102867978A/en
Application granted granted Critical
Publication of CN102867978B publication Critical patent/CN102867978B/en
Expired - Fee Related legal-status Critical Current
Anticipated expiration legal-status Critical

Links

Classifications

    • Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
    • Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
    • Y02E—REDUCTION OF GREENHOUSE GAS [GHG] EMISSIONS, RELATED TO ENERGY GENERATION, TRANSMISSION OR DISTRIBUTION
    • Y02E60/00—Enabling technologies; Technologies with a potential or indirect contribution to GHG emissions mitigation
    • Y02E60/30—Hydrogen technology
    • Y02E60/50—Fuel cells

Landscapes

  • Hybrid Cells (AREA)
  • Fuel Cell (AREA)
  • Inert Electrodes (AREA)
  • Battery Electrode And Active Subsutance (AREA)

Abstract

The invention relates to a flow energy storage battery structure, characterized in that an infill panel is arranged between a bipolar plate and a porous electrode in an electrode frame, the infill panel is made from carbon materials with good electrical conductivity and low porosity or metal materials which are stable in acidic mediums, reduces the body resistances of the electrodes and electrolyte and contact resistance between the electrode bipolar plates to finally reduce the ohmic resistance of the flow energy storage battery. According to the invention, the energy efficiency and voltage efficiency of the flow energy storage battery are raised, so that the working current density is raised, and the weight, volume and cost of the battery with same output power are greatly reduced.

Description

一种液流储能电池结构A liquid flow energy storage battery structure

技术领域 technical field

本发明涉及液流储能电池技术领域,特别涉及一种全钒液流储能电池结构。The invention relates to the technical field of liquid flow energy storage batteries, in particular to a structure of an all-vanadium flow energy storage battery.

背景技术 Background technique

全钒液流储能电池因其具有输出功率和容量相互独立,系统设计灵活;能量效率高,寿命长,运行稳定性和可靠性高,自放电低;选址自由度大,无污染、维护简单,运营成本低,安全性高等优点,在规模储能方面具有广阔的发展前景,被认为是解决太阳能、风能等可再生能源发电系统随机性和间歇性非稳态特征的有效方法,在可再生能源发电和智能电网建设中有着重大需求。All-vanadium redox flow energy storage battery has independent output power and capacity, flexible system design; high energy efficiency, long life, high operation stability and reliability, low self-discharge; large degree of freedom in site selection, no pollution, easy maintenance It has the advantages of simplicity, low operating cost, and high safety. It has broad development prospects in large-scale energy storage. It is considered to be an effective method to solve the random and intermittent unsteady characteristics of renewable energy generation systems such as solar energy and wind energy. There are significant demands in renewable energy power generation and smart grid construction.

然而,全钒液流储能电池运行的工作电流密度较低(<100mA/cm2),仅为质子交换膜燃料电池工作电流密度的十分之一,造成电池模块体积大,材料需求量大,成本高。而工作电流密度的提高可以提高电池的功率密度,降低整个系统的成本,减少储能系统的占地面积和空间,提高其环境适应能力及系统的可移动性,扩展液流储能电池的应用领域。However, the working current density of all vanadium redox flow energy storage battery is low (<100mA/cm 2 ), which is only one-tenth of the working current density of proton exchange membrane fuel cell, resulting in large battery module volume and large demand for materials ,high cost. The increase in working current density can increase the power density of the battery, reduce the cost of the entire system, reduce the footprint and space of the energy storage system, improve its environmental adaptability and system mobility, and expand the application of flow energy storage batteries. field.

由于全钒液流储能电池的电流效率随着工作电流密度的提高而增大,因此提高电池的工作电流密度需要将电压效率保持在一个较高的值,即尽可能地减小电池极化,降低电压损耗。造成电压效率的极化主要包括欧姆极化、电化学极化和浓差极化。Since the current efficiency of the all-vanadium redox flow energy storage battery increases with the increase of the working current density, increasing the working current density of the battery requires keeping the voltage efficiency at a high value, that is, reducing the battery polarization as much as possible. , reduce voltage loss. Polarization that causes voltage efficiency mainly includes ohmic polarization, electrochemical polarization and concentration polarization.

目前已公开的专利文献中针对减小电池极化的方法主要有:The methods for reducing battery polarization in the published patent literature mainly include:

(1)对电极材料如石墨毡、碳纸等进行金属化或氧化改性处理,在碳纤维表面修饰上金属离子或者含氧官能团,提高电极的电催化活性,减小电池的电化学极化,如专利CN 101465417A和CN 101182678A中公开的对石墨毡进行电化学氧化的方法。但该种方法只是减小了电池的电化学极化,对减小电池的欧姆极化没有帮助。而欧姆极化的减小对于提高电池的工作电流密度而言更加重要,因为电化学极化与电流的对数成正比,而欧姆电压降则和电流的大小成正比。因此,随着工作电流密度的提高,电池欧姆内阻的影响会越来越大。(1) Metallize or oxidize electrode materials such as graphite felt, carbon paper, etc., and modify the surface of carbon fibers with metal ions or oxygen-containing functional groups to improve the electrocatalytic activity of the electrode and reduce the electrochemical polarization of the battery. As disclosed in patents CN 101465417A and CN 101182678A, graphite felt is electrochemically oxidized. However, this method only reduces the electrochemical polarization of the battery, and does not help to reduce the ohmic polarization of the battery. The reduction of ohmic polarization is more important to improve the working current density of the battery, because the electrochemical polarization is proportional to the logarithm of the current, and the ohmic voltage drop is proportional to the magnitude of the current. Therefore, as the operating current density increases, the impact of the ohmic internal resistance of the battery will become greater and greater.

(2)研究和开发电极与双极板一体化的复合电极,即一体化电极双极板来降低电极双极板间的接触电阻。如CN 101009376A中公开的,将双极板与多孔电极通过导电粘结材料粘结在一起形成一体化电极双极板。然而,全钒液流储能电池的欧姆内阻主要包括电极、双极板、电解液和隔膜的本体电阻以及电极与双极板间的接触电阻。该方法只是减小了电极双极板间的接触电阻,对占电池内阻比重较大的电极和电解液的本体电阻并无影响,因此对于电压效率和能量效率的提高程度有限。(2) Research and develop composite electrodes that integrate electrodes and bipolar plates, that is, integrated electrode bipolar plates to reduce the contact resistance between electrode bipolar plates. As disclosed in CN 101009376A, the bipolar plate and the porous electrode are bonded together by a conductive bonding material to form an integrated electrode bipolar plate. However, the ohmic internal resistance of the all-vanadium redox flow energy storage battery mainly includes the bulk resistance of the electrodes, bipolar plates, electrolyte and separator, and the contact resistance between the electrodes and the bipolar plates. This method only reduces the contact resistance between the electrode bipolar plates, and has no effect on the bulk resistance of the electrodes and the electrolyte, which account for a large proportion of the internal resistance of the battery, so the improvement of the voltage efficiency and energy efficiency is limited.

发明内容 Contents of the invention

本发明目的在于提供一种液流储能电池结构。The purpose of the present invention is to provide a liquid flow energy storage battery structure.

为实现上述目的,本发明采用的技术方案为:To achieve the above object, the technical solution adopted in the present invention is:

一种液流储能电池结构,电池包括双极板和电极,在双极板与电极之间设置有填充板。A liquid flow energy storage battery structure, the battery includes a bipolar plate and an electrode, and a filling plate is arranged between the bipolar plate and the electrode.

所述填充板为导电性良好、孔隙率低的碳素类材料和/或在酸性介质中稳定的金属材料。填充板的设置可充分利用双极板和多孔电极表面的导电点,达到降低接触电阻的目的;并相应减小多孔电极的厚度,降低电极的本体电阻;同时利用填充材料孔隙率低的特点减少电解液在电池中的存储量以降低电解液的本体电阻,最终达到降低电池欧姆内阻的目的。The filling plate is a carbon material with good conductivity and low porosity and/or a metal material stable in acidic medium. The setting of the filling plate can make full use of the conductive points on the surface of the bipolar plate and the porous electrode to reduce the contact resistance; and correspondingly reduce the thickness of the porous electrode and reduce the bulk resistance of the electrode; at the same time, the low porosity of the filling material can reduce the contact resistance. The storage capacity of the electrolyte in the battery is to reduce the body resistance of the electrolyte, and finally achieve the purpose of reducing the ohmic internal resistance of the battery.

所述碳素类材料为无孔石墨板、柔性石墨板、高碳纤维体积分数的石墨毡或高碳纤维体积分数的碳毡;金属材料为钛板或不锈钢板。The carbon material is non-porous graphite plate, flexible graphite plate, graphite felt with high carbon fiber volume fraction or carbon felt with high carbon fiber volume fraction; the metal material is titanium plate or stainless steel plate.

所述高碳纤维体积分数的石墨毡或高碳纤维体积分数的碳毡的高碳纤维体积分数为10-60%,优选30%-60%。The high carbon fiber volume fraction of the high carbon fiber volume fraction graphite felt or the high carbon fiber volume fraction carbon felt is 10-60%, preferably 30%-60%.

所述电池还包括有电极框,所述填充板厚度为电极框厚度的5-80%,其长度和宽度与电极的尺寸相当。The battery also includes an electrode frame, the thickness of the filling plate is 5-80% of the thickness of the electrode frame, and its length and width are equivalent to the size of the electrode.

所述填充板可以为一整体板材,或由二个以上相同尺寸规格的板材直接叠加而成、或者由二个以上相同尺寸规格的板材通过热压而成。The filling board can be an integral board, or formed by direct stacking of two or more boards of the same size and specification, or formed by hot pressing of two or more boards of the same size and specification.

为减小电解液流动阻力,所述填充板表面可以加工成蛇形或平行流道,进一步减小电解液流动阻力,更利于电解液的流通。In order to reduce the flow resistance of the electrolyte, the surface of the filling plate can be processed into serpentine or parallel flow channels, which further reduces the flow resistance of the electrolyte and is more conducive to the circulation of the electrolyte.

组装电池时,所述碳素材料或金属材料可以直接放置在电极框中,然后再在其上放置多孔电极而成;也可以先将所述碳素类材料或金属材料与双极板压成一体后,再放置电极框、电极组装。When assembling the battery, the carbon material or metal material can be placed directly in the electrode frame, and then the porous electrode is placed on it; it is also possible to press the carbon material or metal material and the bipolar plate first After integration, place the electrode frame and assemble the electrodes.

本发明的有益效果如下:The beneficial effects of the present invention are as follows:

(1)采用本发明的电池结构,由于在双极板与多孔电极之间使用了导电性良好、孔隙率低的碳素材料或金属材料的填充板,使得双极板与填充板及多孔电极与填充板间的接触点位均为导电点,从而能够最大程度的利用双极板与多孔电极表面的导电点位,构筑更好的导电网络,降低电极双极板间的接触电阻;(1) Adopt the battery structure of the present invention, owing to have used the filling plate of good conductivity, low porosity carbon material or metal material between bipolar plate and porous electrode, make bipolar plate and filling plate and porous electrode The contact points with the filling plate are all conductive points, so that the conductive points on the surface of the bipolar plate and the porous electrode can be utilized to the greatest extent to build a better conductive network and reduce the contact resistance between the electrode bipolar plates;

(2)采用本发明的电池结构,由于在双极板与多孔电极之间放置了孔隙率低的碳素材料或金属材料的填充板,减少了电解液在电池中的存储量以降低电解液的本体电阻;并相应减小了多孔电极的厚度,降低了电极的本体电阻,从多个方面降低了电池的欧姆内阻,从而减小欧姆极化,提高了液流储能电池的能量效率和电压效率,从而提高了其工作电流密度,使得相同输出功率的电池重量、体积以及成本均大大降低。(2) Adopt the battery structure of the present invention, because the filling board of carbon material or metal material with low porosity is placed between the bipolar plate and the porous electrode, reduce the storage capacity of electrolyte in the battery to reduce electrolyte body resistance; and correspondingly reduce the thickness of the porous electrode, reduce the body resistance of the electrode, reduce the ohmic internal resistance of the battery from many aspects, thereby reducing the ohmic polarization and improving the energy efficiency of the flow energy storage battery And voltage efficiency, thereby improving its working current density, so that the weight, volume and cost of batteries with the same output power are greatly reduced.

(3)采用本发明电池结构的液流储能电池,在能量效率保持在80%以上的前提下,工作电流密度可以提高到120mA/cm2,使得相同输出功率的电池重量、体积以及成本均大大降低;(3) The flow energy storage battery adopting the battery structure of the present invention can increase the working current density to 120mA/cm 2 under the premise that the energy efficiency is kept above 80%, so that the weight, volume and cost of the battery with the same output power are equal. Greatly reduced;

(4)本发明结构简单,易于操作组装,所使用的填充物可以为廉价易得的碳素材料,具有商业化推广应用价值。(4) The present invention has a simple structure, is easy to operate and assemble, and the filler used can be cheap and easy-to-obtain carbon materials, which has commercial promotion and application value.

附图说明 Description of drawings

图1为本发明液流储能电池的单电池结构示意图;Fig. 1 is a schematic diagram of the single cell structure of the liquid flow energy storage battery of the present invention;

其中:1电池端板;2集流板(双极板);3密封垫片;4电极框;5填充板;6电极;7离子交换膜;Among them: 1 battery end plate; 2 current collector plate (bipolar plate); 3 sealing gasket; 4 electrode frame; 5 filling plate; 6 electrode; 7 ion exchange membrane;

图2为本发明实施例1中单电池在不同电流密度下的充放电曲线图;2 is a charge-discharge curve diagram of a single cell at different current densities in Example 1 of the present invention;

图3为实施例1中单电池与采用原有结构的单电池在开路状态下的交流阻抗谱图。FIG. 3 is an AC impedance spectrum of the single cell in Example 1 and the single cell with the original structure in an open circuit state.

具体实施方式 Detailed ways

下面通过具体实施例详述本发明。The present invention is described in detail below by specific examples.

一种液流储能电池结构,电池包括双极板、电极、膜。其中双极板和电极之间设置有填充板,如图1所示,在电极框4内双极板2与电极6之间放置填充板5。A liquid flow energy storage battery structure, the battery includes a bipolar plate, an electrode, and a membrane. A filling plate is arranged between the bipolar plate and the electrodes. As shown in FIG. 1 , a filling plate 5 is placed between the bipolar plate 2 and the electrode 6 in the electrode frame 4 .

实施例1Example 1

按照图1所示的结构组装成全钒液流储能单电池,其中电极框4为3mm厚,填充板5使用2mm厚的无孔石墨板,电极6为3mm厚的碳毡,无孔石墨板和碳毡的面积均为12cm2,密封垫片3为0.5mm厚的硅橡胶;初始正极电解液为1.5M VO2+的3M H2SO4溶液40ml,初始负极电解液为1.5M V3+的3MH2SO4溶液40ml。电池充电中止电压为1.55V,放电中止电压为0.9V。该电池在不同电流密度下的充放电曲线及电池效率如图2和表1所示。采用本发明电池结构的单电池,电流密度为80mA/cm2时,电压效率和能量效率分别为90%和85.4%;电流密度提高到120mA/cm2时,电压效率和能量效率仍然保持在85.3%和82%。According to the structure shown in Figure 1, an all-vanadium liquid flow energy storage single cell is assembled, wherein the electrode frame 4 is 3 mm thick, the filler plate 5 is a non-porous graphite plate with a thickness of 2 mm, and the electrode 6 is a carbon felt with a thickness of 3 mm, and a non-porous graphite plate. The areas of carbon felt and carbon felt are both 12cm 2 , the sealing gasket 3 is 0.5mm thick silicone rubber; the initial positive electrode electrolyte is 40ml of 1.5M VO 2+ 3M H 2 SO 4 solution, and the initial negative electrode electrolyte is 1.5M V 3+ 40ml of 3M H 2 SO 4 solution. The battery charge termination voltage is 1.55V, and the discharge termination voltage is 0.9V. The charge-discharge curves and battery efficiencies of the battery at different current densities are shown in Figure 2 and Table 1. For a single cell using the battery structure of the present invention, when the current density is 80mA/cm 2 , the voltage efficiency and energy efficiency are 90% and 85.4% respectively; when the current density is increased to 120mA/cm 2 , the voltage efficiency and energy efficiency remain at 85.3% % and 82%.

图2是采用本发明结构的单电池与不使用填充板的单电池在开路状态下的交流阻抗谱图。从中可以看出,采用原有电池结构的单电池欧姆内阻为817m Ωcm2,而采用本发明的电池结构,单电池的欧姆内阻明显减小,仅为614m Ωcm2,与原有电池结构相比,减小了25%。Fig. 2 is an AC impedance spectrogram of a single cell adopting the structure of the present invention and a single cell without a filler plate in an open circuit state. It can be seen that the ohmic internal resistance of the single cell using the original battery structure is 817m Ωcm 2 , but with the battery structure of the present invention, the ohmic internal resistance of the single cell is significantly reduced to only 614m Ωcm 2 , which is different from the original battery structure compared to a 25% reduction.

实施例2Example 2

按照图1所示的结构组装成全钒液流储能单电池,其中电极框4为3mm厚,填充板5使用2mm厚的柔性石墨板,柔性石墨板密度为1.5g/cm3,多孔电极6为3mm厚的碳毡,柔性石墨板和碳毡的面积均为12cm2,密封垫片3为0.5mm厚的硅橡胶;初始正极电解液为1.5M VO2+的3M H2SO4溶液40ml,初始负极电解液为1.5M V3+的3M H2SO4溶液40ml。电池充电中止电压为1.55V,放电中止电压为0.9V。According to the structure shown in Figure 1, an all-vanadium liquid flow energy storage single cell is assembled, wherein the electrode frame 4 is 3mm thick, the filling plate 5 is a 2mm thick flexible graphite plate, the density of the flexible graphite plate is 1.5g/cm 3 , and the porous electrode 6 3mm thick carbon felt, the area of the flexible graphite plate and the carbon felt is 12cm 2 , the sealing gasket 3 is 0.5mm thick silicon rubber; the initial positive electrode electrolyte is 40ml of 3M H 2 SO 4 solution of 1.5M VO 2+ , the initial negative electrode electrolyte is 40ml of 1.5M V 3+ 3M H 2 SO 4 solution. The battery charge termination voltage is 1.55V, and the discharge termination voltage is 0.9V.

本实施例单电池在不同电流密度下的电池效率如表1所示,电流密度提高到120mA/cm2时,电压效率和能量效率仍然保持在84.3%和81.4%。The cell efficiencies of the single cells of this embodiment at different current densities are shown in Table 1. When the current density increases to 120mA/cm 2 , the voltage efficiency and energy efficiency remain at 84.3% and 81.4%.

实施例3Example 3

按照图1所示的结构组装成全钒液流储能单电池,其中电极框4为3mm厚,填充板5使用1mm厚的柔性石墨板,柔性石墨板密度为1.5g/cm3,多孔电极6为4mm厚的碳毡,柔性石墨板和碳毡的面积均为12cm2,密封垫片3为0.5mm厚的硅橡胶;初始正极电解液为1.5M VO2+的3M H2SO4溶液40ml,初始负极电解液为1.5M V3+的3M H2SO4溶液40ml。电池充电中止电压为1.55V,放电中止电压为0.9V。According to the structure shown in Figure 1, an all-vanadium liquid flow energy storage single cell is assembled, in which the electrode frame 4 is 3mm thick, the filling plate 5 is a 1mm thick flexible graphite plate, the density of the flexible graphite plate is 1.5g/cm 3 , and the porous electrode 6 4mm thick carbon felt, the area of the flexible graphite plate and carbon felt is 12cm 2 , the sealing gasket 3 is 0.5mm thick silicon rubber; the initial positive electrode electrolyte is 1.5M VO 2+ 3M H 2 SO 4 solution 40ml , the initial negative electrode electrolyte is 40ml of 1.5M V 3+ 3M H 2 SO 4 solution. The battery charge termination voltage is 1.55V, and the discharge termination voltage is 0.9V.

本实施例单电池在不同电流密度下的电池效率如表1所示,电流密度提高到120mA/cm2时,电压效率和能量效率保持在82.4%和79.9%。The cell efficiencies of the single cells of this embodiment at different current densities are shown in Table 1. When the current density increases to 120mA/cm 2 , the voltage efficiency and energy efficiency remain at 82.4% and 79.9%.

实施例4Example 4

按照图1所示的结构组装成全钒液流储能单电池,其中电极框4为3mm厚,填充板5使用3mm厚的石墨毡,多孔电极6为3mm厚的碳毡,石墨毡和碳毡的面积均为12cm2,密封垫片3为0.5mm厚的硅橡胶;初始正极电解液为1.5M VO2+的3M H2SO4溶液40ml,初始负极电解液为1.5M V3+的3M H2SO4溶液40ml。电池充电中止电压为1.55V,放电中止电压为0.9V。According to the structure shown in Figure 1, an all-vanadium liquid flow energy storage single cell is assembled, wherein the electrode frame 4 is 3mm thick, the filler plate 5 uses 3mm thick graphite felt, the porous electrode 6 is 3mm thick carbon felt, graphite felt and carbon felt The area of each is 12cm 2 , the sealing gasket 3 is 0.5mm thick silicone rubber; the initial positive electrode electrolyte is 40ml of 3M H 2 SO 4 solution of 1.5M VO 2+ , and the initial negative electrode electrolyte is 1.5M V 3+ of 3M H 2 SO 4 solution 40ml. The battery charge termination voltage is 1.55V, and the discharge termination voltage is 0.9V.

本实施例单电池在不同电流密度下的电池效率如表1所示,电流密度提高到120mA/cm2时,电压效率和能量效率仍然保持在80.9%和83.6%。表1为实施例1-4中全钒液流储能单电池在不同电流密度下的电池效率比较。The cell efficiencies of the single cell in this embodiment at different current densities are shown in Table 1. When the current density increases to 120mA/cm 2 , the voltage efficiency and energy efficiency remain at 80.9% and 83.6%. Table 1 is a comparison of the battery efficiencies of the all-vanadium flow energy storage cells in Examples 1-4 at different current densities.

本发明在电极框内双极板与多孔电极之间放置填充板,填充板为导电性好、孔隙率低的碳素材料或者在酸性介质中稳定的金属材料,降低了电极和电解液的本体电阻以及电极双极板间的接触电阻,最终降低了液流储能电池的欧姆内阻。本发明提高了液流储能电池的能量效率和电压效率,从而提高了其工作电流密度,使得相同输出功率的电池重量、体积以及成本均大大降低。In the present invention, a filling plate is placed between the bipolar plate and the porous electrode in the electrode frame. The filling plate is a carbon material with good conductivity and low porosity or a metal material stable in acidic medium, which reduces the bulk of the electrode and the electrolyte. The resistance and the contact resistance between the electrode bipolar plates finally reduce the ohmic internal resistance of the flow energy storage battery. The invention improves the energy efficiency and voltage efficiency of the liquid flow energy storage battery, thereby increasing its working current density, so that the weight, volume and cost of the battery with the same output power are greatly reduced.

Claims (6)

1.一种液流储能电池结构,电池包括双极板、电极框和电极,其特征在于:在电极框内双极板与多孔电极之间设置有填充板,所述填充板厚度为电极框厚度的5-80%,其长度和宽度与电极的尺寸相当;电极为碳毡,碳毡厚度为3mm,填充板厚度为2mm,电极框厚度为3mm;所述填充板为导电性良好、孔隙率低的碳素类材料和/或酸性介质中稳定的金属材料。1. A liquid flow energy storage battery structure, the battery includes a bipolar plate, an electrode frame and an electrode, and is characterized in that: a filling plate is arranged between the bipolar plate and the porous electrode in the electrode frame, and the thickness of the filling plate is the electrode 5-80% of the thickness of the frame, its length and width are equivalent to the size of the electrode; the electrode is carbon felt, the thickness of the carbon felt is 3mm, the thickness of the filling plate is 2mm, and the thickness of the electrode frame is 3mm; the filling plate is good in conductivity, Carbonaceous materials with low porosity and/or metallic materials stable in acidic media. 2.根据权利要求1所述的电池结构,其特征在于:所述碳素类材料为无孔石墨板、柔性石墨板、高碳纤维体积分数的石墨毡或高碳纤维体积分数的碳毡;耐酸性金属材料为钛板或不锈钢板。2. The battery structure according to claim 1, characterized in that: the carbonaceous material is a non-porous graphite plate, a flexible graphite plate, a graphite felt with a high carbon fiber volume fraction or a carbon felt with a high carbon fiber volume fraction; acid-resistant The metal material is titanium plate or stainless steel plate. 3.根据权利要求2所述的电池结构,其特征在于:所述高碳纤维体积分数的石墨毡或高碳纤维体积分数的碳毡的高碳纤维体积分数为10-60%。3. The battery structure according to claim 2, wherein the high carbon fiber volume fraction of the high carbon fiber volume fraction graphite felt or the high carbon fiber volume fraction carbon felt is 10-60%. 4.根据权利要求1所述的电池结构,其特征在于:所述填充板为一整体板材,或由二个以上相同尺寸规格的板材直接叠加而成、或者由二个以上相同尺寸规格的板材通过热压而成。4. The battery structure according to claim 1, characterized in that: the filler plate is an integral plate, or is formed by directly stacking two or more plates of the same size and specification, or is composed of two or more plates of the same size and specification Made by hot pressing. 5.根据权利要求1所述的电池结构,其特征在于:所述填充板表面设置有蛇形或平行流道。5. The battery structure according to claim 1, characterized in that: serpentine or parallel flow channels are provided on the surface of the filling plate. 6.根据权利要求1所述的电池结构,其特征在于:所述电池为全钒液流储能电池、锌溴液流电池、多硫化钠溴液流电池或锡钒液流电池。6. The battery structure according to claim 1, wherein the battery is an all-vanadium flow energy storage battery, a zinc-bromine flow battery, a sodium polysulfide-bromine flow battery or a tin-vanadium flow battery.
CN201110186221.9A 2011-07-05 2011-07-05 Flow energy storage battery structure Expired - Fee Related CN102867978B (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
CN201110186221.9A CN102867978B (en) 2011-07-05 2011-07-05 Flow energy storage battery structure

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
CN201110186221.9A CN102867978B (en) 2011-07-05 2011-07-05 Flow energy storage battery structure

Publications (2)

Publication Number Publication Date
CN102867978A CN102867978A (en) 2013-01-09
CN102867978B true CN102867978B (en) 2015-06-03

Family

ID=47446681

Family Applications (1)

Application Number Title Priority Date Filing Date
CN201110186221.9A Expired - Fee Related CN102867978B (en) 2011-07-05 2011-07-05 Flow energy storage battery structure

Country Status (1)

Country Link
CN (1) CN102867978B (en)

Cited By (1)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
US12658450B2 (en) 2021-12-10 2026-06-16 Uop Llc Current collector for redox flow batteries

Families Citing this family (9)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN104716392B (en) * 2013-12-15 2018-09-21 中国科学院大连化学物理研究所 A kind of flow battery structure
CN103682395B (en) * 2013-12-24 2016-08-17 大连融科储能技术发展有限公司 A flow battery stack and a flow battery system
CN106876745B (en) * 2015-12-12 2019-05-21 中国科学院大连化学物理研究所 A bipolar plate for flow battery with variable speed flow channel
CN106887612B (en) * 2015-12-12 2020-04-07 中国科学院大连化学物理研究所 Bipolar plate with serpentine flow channel and application of bipolar plate in all-vanadium redox flow battery
KR102127037B1 (en) 2017-02-28 2020-06-25 주식회사 엘지화학 Electrode structure and redox flow battery comprising the same
CN108666594A (en) * 2018-04-03 2018-10-16 华东师范大学 A kind of bipolar plates manufacture craft
CN108598543B (en) * 2018-06-27 2021-07-06 西安交通大学 a flow battery
CN109713339B (en) * 2018-12-13 2020-08-14 浙江大学 A flow battery system control method based on current optimization strategy
CN110600750B (en) * 2019-09-25 2022-12-09 江苏恒安储能科技有限公司 All-vanadium redox flow battery composite terminal electrode and preparation method thereof

Citations (1)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN101877408A (en) * 2009-04-30 2010-11-03 比亚迪股份有限公司 A current collector of a flow battery and a flow battery

Patent Citations (1)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN101877408A (en) * 2009-04-30 2010-11-03 比亚迪股份有限公司 A current collector of a flow battery and a flow battery

Cited By (2)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
US12658450B2 (en) 2021-12-10 2026-06-16 Uop Llc Current collector for redox flow batteries
AU2022405518B2 (en) * 2021-12-10 2026-07-30 Uop Llc Current collector for redox flow batteries

Also Published As

Publication number Publication date
CN102867978A (en) 2013-01-09

Similar Documents

Publication Publication Date Title
CN106558704B (en) A kind of gradient electrode for flow battery and its application
CN102479968B (en) Zinc / polyhalide energy storage cell
CN104716392B (en) A kind of flow battery structure
CN102867978A (en) Flow energy storage battery structure
CN101997129B (en) Liquid flow battery
CN106876765B (en) A flow battery stack
CN101719556B (en) Stack structure of redox flow battery
CN103633330B (en) A kind of flow battery combination electrode and liquid flow energy storage battery
CN101587959A (en) Electrode frame and all-vanadium redox flow energy storage battery stack
CN207587857U (en) A kind of zinc-nickel single flow battery
CN102569833A (en) Bipolar plate of redox flow battery
CN201549546U (en) A columnar flow battery device
CN104143646A (en) Flow energy storage cell or pile running method
CN106981371A (en) A kind of water system electrolyte super capacitance cell
CN108598543A (en) A kind of flow battery
CN106532093A (en) Quinone metal redox couple flow cell system
CN206349448U (en) A kind of pile of redox flow batteries
WO2016078492A1 (en) Quinone polyhalide flow battery
CN201514973U (en) A flow battery
CN103545539A (en) Three-dimensional netted graphite foam or netted glassy carbon bipolar plate of all-vanadium redox flow battery
CN101127407A (en) Portable proton exchange membrane fuel cell stack with hydrothermal self-management
CN104900898A (en) A method for reducing capacity fading of vanadium batteries
CN213304190U (en) Flow battery plate frame
CN115911439A (en) A bipolar plate flow channel with a double helix structure for a flow battery
CN115472883A (en) Design method and application of all-vanadium redox flow battery electrolyte with high capacity retention rate

Legal Events

Date Code Title Description
C06 Publication
PB01 Publication
C10 Entry into substantive examination
SE01 Entry into force of request for substantive examination
C14 Grant of patent or utility model
GR01 Patent grant
CF01 Termination of patent right due to non-payment of annual fee

Granted publication date: 20150603

Termination date: 20210705

CF01 Termination of patent right due to non-payment of annual fee